Poststernotomy Mediastinitis and the Role of Broken Steel Wires: Retrospective Study. Issue 3 (May 2013) - Meeks, Michelle D.M.E.; Lozekoot, Pieter W.J.; Verstraeten, Stefan E.; Nelis, Mischa; Maessen, Jos G.
Objective: Mediastinitis is a severe complication of cardiac surgery. Sternal instability is concomitantly present in most cases. Broken steel wires may cause sternal instability. In this study, the role of broken steel wires in sternal closure was evaluated in patients who developed poststernotomy mediastinitis. Methods: Preoperative, perioperative, and postoperative data of patients who underwent thoracic surgery between 1996 and 2006 were retrieved from the SUMMIT registry database. Patients needing reoperation for mediastinitis were identified. Patients' charts and chest radiographs from initial surgery to reoperation for mediastinitis were reviewed. Results: Forty-five patients developed postoperative mediastinitis needing reoperation (0.6%). Because of loss to follow-up, 31 patients were evaluated. Eight patients (25.8%) presented fractured steel wires. Most of the broken steel wires (87.5%) manifested at the cranial site of figure-of-eight configurations. In the patients without broken steel wires, mediastinitis manifested after 14 days compared with 38 days in the patients with broken wires. Time until mediastinitis was not significantly different (P = 0.229). The mean time until steel wire disruption was 14 days (range, 4–48 days). Conclusions: Broken steel wires were observed before mediastinitis became manifest. Fracturing occurred mainly at the cranial site of figure-of-eight configurations. The results of the present study emphasize that closure technique plays a prominent role in the development of mediastinitis. Because mediastinitis is associated with an increased risk for early morbidity, attention should be paid to patients presenting with broken steel wires. New techniques for median sternotomy closure are needed that are less prone to mechanical fatigue than are steel wires.